PENINGKATAN KESADARAN HUKUM SISWA TENTANG LARANGAN BULLYING MELALUI PEMBELAJARAN PPKn (STUDI KUANTITATIF DI SMA NEGERI 1 SALIMPAUNG) - Feby Okta Marlia Syafri; Budi Juliardi; Indra Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying remains a persistent issue in schools, causing negative impacts on students’ psychological well-being, social relationships, and learning processes. Civic Education (Pancasila and Citizenship Education/PPKn) plays a strategic role in fostering students’ legal awareness by instilling legal values, responsibility, and respect for the rights of others, thereby helping to prevent bullying behavior. This study aimed to analyze the effect of PPKn learning on improving students’ legal awareness regarding the prohibition of bullying at SMA Negeri 1 Salimpaung. The study employed a quantitative approach using a survey method. The sample consisted of 75 eleventh-grade students selected through proportional random sampling. Data were collected using a Likert-scale questionnaire that had met validity and reliability requirements and were analyzed using descriptive statistics and simple linear regression. The findings revealed that PPKn learning was categorized as good and had a positive and significant effect on students’ legal awareness regarding the prohibition of bullying (Sig. 0.000 < 0.05). These findings indicate that better implementation of PPKn learning is associated with higher levels of students’ legal awareness, thereby supporting efforts to prevent bullying in the school environment.